Universidade, saúde mental e direitos humanos: uma análise institucional a partir das vivências dos estudantes da Universidade Federal do Tocantins - Bernardes, Luzia Vieira da Silva (Universidade Federal do Tocantins, 2021)
This study proposes an institutional analysis of public policies for the promotion of mental health at the Universidade Federal do Tocantins. From listening to university graduate students and the theoretical reference, sought out to understand the complexity of the mental health issue related to human rights. An applied, exploratory, field research was then carried out, adapted to the context of the new coronavirus pandemic, based on bibliographical and qualitative references. Data collection occurred through semi-structured deconstruction, in the period between September 2020 and February 2021, with the approval of the Comitê de Ética em Pesquisas. The results were analyzed based on the institutional analytical approach described by Baremblitt (2002), observing the phenomenon from the subject and considering their role in the social context of the university. The sample consisted of 08 students from undergraduate courses at the Campus Universitário de Palmas, regularly enrolled. Among the results we highlight the reports that refer to situations of suffering aggravated by the pandemic context, the profile of the participants that confirms the picture of socioeconomic vulnerabilities pointed out by the theoretical reference, as well as a low demand or adherence of students to the promotion and mental health care actions promoted at the Campus de Palmas. There is also a mismatch of knowledge of sectors and services within the university, which provide host students, which indicates difficulties with communication between the institution and the academic community and the lack of delineation of the mental health policy of the university. Since, if such a policy exists, it is not clearly delimited and accessible. Based on the results, a booklet was elaborated as a technical product on the themes of mental health, human rights and care and reception services in the university and in the public health network. It is expected that the results of this research will contribute to the improvement of actions aimed at the prevention of psychological distress and may contribute, in some measure, to provide students with resources and guidance for mental health care in their academic trajectory, in addition to stimulating the production of scientific knowledge related to human rights and mental health of students in public universities.